A jumble of needs : women's activism and neoliberalism in the colonias of the Southwest - Dolhinow, Rebecca (University of Minnesota Press, 2010)
Many immigrant communities along the U.S. border with Mexico are colonias, border settlements lacking infrastructure or safe housing. A Jumble of Needs examines the leadership of Mexican women immigrants in three colonias in New Mexico, documenting the role of NGOs in shaping women's activism in these communities. Ethnographer Rebecca Dolhinow, who worked in the colonias, uncovers why such attempts to exercise political agency are so rarely successful.